The social life of the malauegs: Recognition of their cultural identity and integrity - Cabrera-Ramos, Chita (International Journal of Psychosocial Rehabilitation, 2020)
This study on the social life among the Malaueg reflects on their present cultural beliefs and practices occurring among the residents of the indigenous cultural communities, particularly the Malauegs of Rizal, Cagayan represented by four barangays namely: Gaddangao, Illuru Norte, Gaggabutan East and Duyun. It focused on the life cycle: conception, birth, childbirth, child rearing, adolescence, courtship, marriage, death and the educational implications of these beliefs and practices.  Result of the study reveals that the Malaueg are people with rich cultural heritage which can shed more valuable facts about the aborigines. No researcher perhaps is likely to discount the details of their beliefs and practices served for survival and existence through the years. Some of the major beliefs includes pregnant woman should undergo paddal if she suffers from unexplainable discomfort; serve walin for their dead relatives whom they believe are witnessing the delivery; burning of braided cloth known as amlang to drive evil spirits; mothers usually heat a kuwid and massaged to the breast of their daughter so the breast will not grow bigger and many other practices on their entire life cycle. It is undeniably observe in the study that the Malauegs cling to the old Malauegs social order or world views as reflected in their cultural traditions and practices are relevant and applicable to their daily needs and problems, thus found to be functional to their lives. For this, majority of the Malauegs ignore or oppose the concepts of social readily available and adopted by the young population. Further, these beliefs and practices have influenced their lives for all these years. Thus the people have kept them prevailing and untainted throughout the years. With this cultural beliefs and practices kept intact, the Malauegs remain to exist as part of the national society but with their own identity and integrity, their structure and their traditions.